Dinamika inflasi di indonesia terhadap daya beli masyarakat dalam perspektif ekonomi makro - Utama, Fera Putri (Maliki Interdisciplinary Journal, 2025)
The economic prosperity of a country is greatly influenced by low and stable inflation rates, which reflect a healthy and stable economic condition. Price stability resulting from controlled inflation helps build confidence among both consumers and businesses. Conversely, when inflation rises sharply or becomes erratic and uncontrollable, it presents serious challenges. High inflation can trigger unpredictable price increases. Developing countries are generally more vulnerable to inflation. An inflation rate below 3% is still considered within a normal range for a country. However, if inflation rises significantly and becomes unstable, it indicates economic instability. This situation is marked by a general and continuous increase in the prices of goods and services, which can ultimately worsen poverty levels and increase unemployment rates. The aim of this study is to determine that one of the factors contributing to the decline in people’s purchasing power is inflation.